Brewing microbiology : managing microbes, ensuring quality and valorising waste - Hill, Annie E. (Woodhead Publishing is an imprint of Elsevier, 2015)
Brewing Microbiology discusses the microbes that are essential to successful beer production and processing, and the ways they can pose hazards in terms of spoilage and sensory quality. The text examines the properties and management of these microorganisms in brewing, along with tactics for reducing spoilage and optimizing beer quality. It opens with an introduction to beer microbiology, covering yeast properties and management, and then delves into a review of spoilage bacteria and other contaminants and tactics to reduce microbial spoilage. Final sections explore the impact of micro.
Keywords: Brewing -- Microbiology.; Brewing -- Quality control.; Brewing industry -- By-products.; elektronické knihy; electronic books